Hubungan Kompetensi Pedadodik Guru dengan Motivasi Belajar Siswa - Adibah Adibah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2019)
This study aims to describe the Pedagogical Competence of Teachers in Improving Student Learning Motivation. This research is descriptive qualitative, whose data sources are carried out by library research, namely reviewing some literature related to the subject matter. While the data analysis technique is done by using descriptive analysis, which is to explain all the data about the teacher's pedagogical competence and student learning motivation, then draw a conclusion. The results of the study show that the Pedagogic Competencies that the teacher has can increase student learning motivation. Which means that student learning motivation is largely determined by the role of the teacher who has pedagogical competence.